Integrating Islamic Values into Early Childhood Education Branding: A Case Study of the Sekolah Plus Ngaji Model in Rural Indonesia - Herni, Sumi; Zuriah, Nurul; Poerwanti, Endang; Tinus, Agus (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the Sekolah Plus Ngaji (SPN) program as a distinctive school branding and promotion strategy in early childhood education (ECE) within rural Indonesia. Responding to increasing competition among ECE institutions, kindergartens are required to design programs that align with parental expectations and community values. This research employed a qualitative case study involving one principal, four teachers, and ten parents at Dharma Wanita Persatuan 1 Kindergarten in Waturejo, Ngantang District, Malang. Data were collected through semi-structured interviews, participant observation of daily SPN activities, and document analysis of school records and promotional media, then analyzed using the interactive model of Miles et al. through data reduction, data display, and conclusion drawing. The findings reveal that the SPN program—which integrates Quranic recitation, memorization of daily prayers, and habituation of Islamic values into the formal kindergarten curriculum—functions not only as a religious education initiative but also as a strategic branding tool that differentiates the school from competitors. Parents consistently highlighted SPN as their primary reason for school selection, corresponding with a 20–30% increase in enrollment over the past two years. The study contributes to the literature on school marketing by showing how faith-based initiatives strengthen school identity, parental trust, and institutional sustainability in resource-limited rural contexts, and it offers a replicable model for other ECE institutions seeking to balance academic, moral, and religious education.